Strategi Operasi dan Penyampaian Jasa serta Dampaknya pada Nilai Jasa dan Kinerja Pemasaran - Juju, Undang (Jurnal Trikonomika, 2010)
The objectives of the study are (1) description market orientation (2) tested explanation on the influence of: market orientation upon service operational delivery strategy; service operational and delivery strategy upon service value; service operational and delivery strategy upon market performance;and service value upon marketing performance. The research methods used in the research are descriptive and explanatory survey at 50 BPRâs in West Java. The data were collected through the interview with marketing division in September until December 2007. Data analysis used Path Analisys and processed with Amos. The result of reseach showed that (1) BPRâs have moderately done market orientation, (2) BPRâs have moderately done service operational strategy and service delivery strategy,. (3) BPRâs service value placed moderate category, (4) BPRâs marketing performance placed low category (5) market orientation has significantly and positively influenced strategy operasional and delivery service, (6) service operational and delivery strategy have significantly and positively influence service value, (7) service operational and delivery strategy have positively and significantly influence upon marketing performance, but partially service operational strategy have negative influenced, (8) service value has positive and significant influence upon marketing performance.